Thrombopoietin activates a STAT5-like factor in hematopoietic cells. - Pallard, C (1995)
Thrombopoietin (TPO) is a newly cloned cytokine which is the major regulator of circulating platelet levels, acting on both proliferation and differentiation of megakaryocytes. We have investigated the ability of TPO to activate the JAK/STAT pathway in megakaryocytic cell lines. We used either the granulocyte-macrophage colony-stimulating factor (GM-CSF)- and/or erythropoietin (EPO)-dependent UT7 cell line in which the murine TPO receptor (mumpl) had been transfected (mumpl-UT7 transfectants) or the MO7E and DAMI cells which express endogenous human TPO receptors. We demonstrated that TPO activates the kinase JAK2 and a STAT5-like transcriptional factor but not STAT1, STAT2, STAT3 or STAT4, in a very rapid and transient manner. In order to better ascertain the specificity of the activation of STAT5-related factor by TPO, we investigated the effect of other cytokines/growth factors. Both GM-CSF and EPO activated the STAT5-like factor. In contrast, neither interferon (IFN)-gamma nor the mitogenic stem cell factor (SCF) activated STAT5, although IFN-gamma did activate STAT1 in those cells. The hematopoietic DNA binding activity related to STAT5 was identified as a p97 tyrosine-phosphorylated protein band which exhibited identical gel mobility to the mammary STAT5. Because v-mpl, a truncated form of the TPO receptor c-mpl, was shown to be oncogenic, we tested the activity of v-mpl on STAT5 and found STAT5 constitutively activated in two different v-mpl-expressing cells, the transiently transfected Cos7 cells and the stable v-mpl-UT7 transfectants. Overall, our data indicate that STAT5 is widely expressed in hematopoietic cells and activated by a number of cytokines, including TPO, GM-CSF and EPO, but not by IFN-gamma or SCF.